A descriptive study on use of family planning methods by married reproductive aged women in Bhutanese refugee camps of eastern Nepal - Rayamajhi, R B; Budhathoki, S S; Ghimire, A; Neupane, B; Paudel, A; Paudel, K M; Pokharel, P K (Journal of Chitwan Medical College, 2017)
Informed choice is an important aspect for decision making regarding the uptake and adherence to family planning methods. The women in Bhutanese Refugee camps of Nepal have family planning services available through the primary health centers located within the refugee camps. Objective: This study was conducted to find out the factors related to use of family planning methods by married women of reproductive age in the Bhutanese Refugee camps of eastern Nepal. Results: The study has a response rate of 100.0%. The mean age of the respondents was 29.3 years. Primary health center of the camp was the most commonly known (60.9%) place for accessing family planning methods. One third of the respondents discussed family planning methods with their husbands. The rest didn’t discuss as they felt intimidated by their husband. Almost 90.0% respondents had ever used a family planning method and the most common reason for using a method was the influence of a peer (62.3%). Conclusion: Further studies on exploring the discussion between husband and wives regarding the use of family planning is needed so that appropriate interventions can be identified. The role of the peer could be further explored to assist women to make an informed choice of their family planning method.